NetOne Cellular Private Limited's underperformance : causes and the way forward - Munyaradzi, Rwakurumbira (Graduate School of Development Policy and Practice, 2016)
This research is a case study analysis of NetOne Cellular (Pvt) Ltd, a state enterprise in the mobile cellular telecommunications industry in Zimbabwe which has failed to perform to government and public expectation since its launch in 1996. At the advent of mobile telecommunications industry in Zimbabwe in the 1990s, it was expected that the Government of Zimbabwe would reap huge revenues in the lucrative telecommunications industry by being the pioneer and monopolising the provision of mobile telecommunications in the country. Government therefore, set up NetOne, initially as a department under the Postal and Telecommunications Corporation (PTC) and later turned it into an incorporated company in 2001. The company has however failed to perform to expectations despite the advantages which usually go with government protection and favouritism in comparison to its competitors Econet Wireless Zimbabwe and Telecel Zimbabwe. This study provides evidence of the company's poor performance, an analysis and discussion of the underlying and proximate causal factors thereto as well as a set of recommendations and possible ways forward. The study seeks to explore and prove that the Zimbabwean political settlements, mismanagement of economic rents, as well as the scourge of poor corporate, undercapitalisation, unfavourable sectoral and regulatory dynamics negatively impact on NetOne's performance. Derived from the foregoing the above are the cascading effects of inadequate leadership and business practices within the organisation which also played a major role in the company's modicum growth and underperformance over the years. It concludes that the Zimbabwe political settlements and failure to manage and effectively exploit political rents is the major contributor to the company's failure and lead to both external and internal poor governance of the company thereby affecting its performance.